(untitled) (Biological Sciences - PJSIR, 2001)
Effects of Benlate fungicide on the efficacy of Bradyrhizobium sp., in the control of root infecting fungi viz., Macro- phaseolina, Rhizoctonia solani andFusarium spp. wereevaluatedunder field conditionson mungbean, soybean, cotton and sunflower. Bradyrhizobium sp., used alone or mixed with Benlate showed good biocontrol and growth promoting effects. Benlate was found as the most effective treatment in the suppression of F. solani infection.